ISMAT BUKHARI’S IMPRESSION FROM THE GAZELS OF SHEIKH KAMALA KHUJANDI (Scientific journal of the Fergana State University, 2023)
Mawlana Khoja Fahruddin Ismatullah ibn Masoud Bukhari is considered an outstanding scientist and poet of the late XIV and early XV centuries. A noble reference to this classic speaker is found in most medieval poems. In this essay we tried to look at his poetic collections from the famous philosopher and poet Sheikh Kamoli Khujandi. In the course of this review, it was found that Ismail Bukhara benefited both from ordinary gazel forms and from its rhyme and use, as well as from expressive and expressive ways of using a particular image of a poem from Kamol Khujandi.